FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA USAHA KECIL DAN MENEGAH (UKM) DI PROVINSI RIAU (Pada Sektor Industri Pengolahan Kelapa Sawit) - Caylina, Elgi; Sari, Ria Nelly; Anugerah, Rita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
Small and medium enterprises (SMEs) have an important role in economic development in Indonesia. The increasing number of SMEs has caused competition to become increasingly fierce. Especially SMEs in the palm oil processing industry sector, because to make SMEs can maintain their existence and expand their business in the face of more severe challenges, appropriate strategies are needed. Performance measurement for SMEs is still not well established such as performance measurement in large companies. This paper aims to determine the factors that affect the performance of SMEs with several variables such as entrepreneurship, innovation, market orientation and sustainability aspects. Thus the method used in this study is a quantitative method by conducting a survey of Small and Medium Enterprises (SMEs) in the palm oil processing industry sector in Riau Province. The results of this study are the variables used in this study where each factor has a significant positive correlation to the performance of SMEs. This research is expected to contribute as literature used by academics and SMEs to effectively measure the performance of SMEs, especially in a competitive environment.